Human roughness perception and possible factors effecting roughness sensation. Issue 3 (25th January 2017) - Aktar, Tugba; Chen, Jianshe; Ettelaie, Rammile; Holmes, Melvin; Henson, Brian
Abstract: Surface texture sensation is significant for business success, in particular for solid surfaces for most of the materials; including foods. Mechanisms of roughness perception are still unknown, especially under different conditions such as lubricants with varying viscosities, different temperatures, or under different force loads during the observation of the surface. This work aims to determine the effect of those unknown factors, with applied sensory tests on 62 healthy participants. Roughness sensation of fingertip was tested under different lubricants including water and diluted syrup solutions at room temperature (25C) and body temperature (37C) by using simple pair‐wise comparison to observe the just noticeable difference threshold and perception levels. Additionally, in this research applied force load during roughness observation was tested with pair‐wise ranking method to illustrate its possible effect on human sensation. Obtained results showed that human's capability of roughness discrimination reduces with increased viscosity of the lubricant, where the influence of the temperature was not found to be significant. Moreover, the increase in the applied force load showed an increase in the sensitivity of roughness discrimination. Observed effects of the applied factors were also used for estimating the oral sensation of texture during eating. These findings are significant for our fundamental understanding to texture perception, and for the development of new food products with controlled textural features. Practical applications: Texture discrimination ability, more specifically roughness discrimination capability, is a significant factor for preference and appreciation for a wide range of materials, including food, furniture, or fabric. To explore the mechanism of sensation capability through tactile senses, it is necessary to identify the relevant factors and define characteristics that dominate the process involved. The results that will be obtained under these principles will be helpful for the industry in the development and optimization of new products, especially for the individuals' with special needs. With this exploratory study, we illustrate differential thresholds of tactile senses under changing conditions of surface lubrication and applied force load. Also, the tests were carried out under different temperatures to understand the oral sensation capability. The results and correlations may provide useful information about texture sensitivity and also methodologies could be applied to general sensory studies.